2022
DOI: 10.1038/s41467-022-33083-5
|View full text |Cite
|
Sign up to set email alerts
|

In situ small-angle X-ray scattering reveals strong condensation of DNA origami during silicification

Abstract: Silicification of DNA origami structures increases their stability and provides chemical protection. Yet, it is unclear whether the whole DNA framework is embedded or if silica just forms an outer shell and how silicification affects the origami’s internal structure. Employing in situ small-angle X-ray scattering (SAXS), we show that addition of silica precursors induces substantial condensation of the DNA origami at early reaction times by almost 10 %. Subsequently, the overall size of the silicified DNA orig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Nevertheless, due to the high cost of PNA, we also explored more sustainable options. Inspired by work by Ding and co-workers [8e] , which showed that TMAPS-TEOS precursors accumulated most favorably on double-stranded DNA (dsDNA) compared to the closely packed dsDNA in a DNA origami nanostructure, we hypothesize that ssDNA may show even less accumulation of silica precursors. We assume that ssDNA, possessing comparatively less phosphate groups compared to dsDNA, may consequently attract less TMAPS molecules.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Nevertheless, due to the high cost of PNA, we also explored more sustainable options. Inspired by work by Ding and co-workers [8e] , which showed that TMAPS-TEOS precursors accumulated most favorably on double-stranded DNA (dsDNA) compared to the closely packed dsDNA in a DNA origami nanostructure, we hypothesize that ssDNA may show even less accumulation of silica precursors. We assume that ssDNA, possessing comparatively less phosphate groups compared to dsDNA, may consequently attract less TMAPS molecules.…”
Section: Resultsmentioning
confidence: 94%
“…We recently showed that DNA origami undergo strong condensation during silicification as a result of hydrophobic effects and water depletion forces caused by the influx of silica into the origami structure. [8g] However, even at the maximally condensed state with sub-nm external silica deposition, structures displayed impressive thermal stability. Therefore, we here employed the same structures (24HB and 4LB) as reported in our recent publication and silicified these following our previously published protocol, using a rotator ( Figures S7,8 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another research direction would be to go beyond imaging and to use the fiducial as a mechanical stiffness marker to study the compliance of biomolecules to indentation forces 60 , e.g. to probe the effects of silicifaction 61, 62 or other functionalization. We, therefore, anticipate that our fiducial will provide a multi-modal calibration platform for a range of applications.…”
Section: Design Of the Dna Origami Fiducial Structurementioning
confidence: 99%